PEMANFAATAN MEDIA SOSIAL INSTAGRAM DALAM PEMBELAJARAN BAHASA INGGRIS PADA SISWA ENGLISH CLUB DI SMPN 163 JAKARTA - Febrimarini Br. Sinulingga; Susanne A.H. Sitohang; Thesalonika Alvina; Adiranto Hia; Mike Wijaya Saragih (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
This paper aims to show the results of the Faculty of Letters and Languages UKI’s Community Service (PkM) focusing on the use of Instagram in learning English for the English Club students of SMPN 163, Jakarta, in the period of August to November 2022. Instagram is a medium used to evaluate students' understanding of the learning material provided by tutors every week. The forms of assignments varied, ranging from making posters, videos, short essays, presentation materials, and greeting cards, which were adjusted to weekly themes, and were carried out both independently and in groups. From the learning evaluation distributed through the Google form, there were 52 respondents consisting of 33 female and 19 male respondents. The survey results show that more than 90% of respondents feel the benefits of using Instagram in the process of learning English, both in terms of improving hard skills and soft skills. The hard skills acquired are related to English skills both spoken and written and skills in making and editing posters and videos, while the soft skills acquired are related to creativity and the ability to work together in a team. The evaluation results also show that more than 80% of English Club participants recommend continuing the use of Instagram social media in the future English learning process. Keywords: English Club; Instagram; hard and soft skills